2010
DOI: 10.1108/13639511011066863
|View full text |Cite
|
Sign up to set email alerts
|

Widening the scope on complaints of police misconduct

Abstract: Purpose -This study aims to examine the relationship between officer characteristics, productivity levels, situational context, the complaint process and allegations of police misconduct in a Midwestern municipal police agency. Design/methodology/approach -Data were collected for all formal and informal complaints filed against patrol officers from 2002-2005. Demographic information, arrest, citation and report data, as well as data regarding the number of officers on scene during the police citizen contact th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Recent studies, though, have revealed less of a sex‐based difference among citizens’ complaints against the police (Bergeron et al. 2008; Hassell and Archbold 2010). One study found that the distribution of formal and informal complaints about male and female police officers was generally representative of their representation within their agency (Bergeron et al.…”
Section: Exploring Similarities and Differences Among Male And Femalementioning
confidence: 99%
“…Recent studies, though, have revealed less of a sex‐based difference among citizens’ complaints against the police (Bergeron et al. 2008; Hassell and Archbold 2010). One study found that the distribution of formal and informal complaints about male and female police officers was generally representative of their representation within their agency (Bergeron et al.…”
Section: Exploring Similarities and Differences Among Male And Femalementioning
confidence: 99%
“…Reviews of complaints against police from across the country show variation in rates at which complaints are sustained; however, most found the rate to be below 12 percent (Dugan and Breda ; Hassell and Archbold ; Hickman ; Liederbach et al. ; Manis, Archbold, and Hassell ; Michelle Lersch and Mieczkowski ; Terrill and Ingram ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…; Manis, Archbold, and Hassell ; Michelle Lersch and Mieczkowski ; Terrill and Ingram ). A 2010 analysis of complaints made against a Midwestern law enforcement agency found that 62 percent of complaints were sustained (Hassell and Archbold ). At the other end of the spectrum, Liederbach et al.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The micro-level studies that have focused more on the police officer typically fall into one of two groups. First, some research has analyzed officers' personal demographics, backgrounds, and/or years and types of experience as they correlate with citizen complaints (Brandl, Stroshine, & Frank, 2001;Harris, 2010;Hassell & Archbold, 2010;Kappeler, Sapp, & Carter, 1992;Lersch, 2002;McElvain & Kposowa, 2004;Terrill & Ingram, 2016). Whereas, fewer studies have focused on officer experiences, perceptions, and attitudes towards the complaint process and/or system (Bartels & Silverman, 2005;De Guzman, 2004;Schaible et al, 2013;Wells & Schafer, 2007).…”
Section: Literature Review On Organizational Studies Of Police Departmentioning
confidence: 99%